First Radiocarbon Chronology for the Early Iron Age Sites of Central Kazakhstan (Tasmola Culture and Korgantas Period). Issue 1 (19th January 2016) - Beisenov, Arman Z; Svyatko, Svetlana V; Kassenalin, Aibar Е; Zhambulatov, Kairat А; Duisenbai, Daniyar; Reimer, Paula J
Abstract: We present the first radiocarbon dates of Early Iron Age sites of central Kazakhstan (in total, 24 dates for 16 recently excavated sites). Archaeologically, the sites have been attributed to the Tasmola culture of the Saka period and later Korgantas phase of the early Hun period. The new accelerator mass spectrometry (AMS) 14 C dates suggest that the majority of analyzed Tasmola sites belong to the beginning of the 8th–5th century cal BC, while Korgantas dates to the 4th–2nd century cal BC. This corresponds with the latest archaeological data for the region; however, it is somewhat contrary to the traditional perception of the chronology of the Scythian period in central Kazakhstan. The new dates suggest the beginning of the Early Scythian period in the region in at least the late 9th or 8th century BC rather than 7th century BC according to the traditional approach.